Trilogi Kecerdasan dan Kaitannya dengan wahyu (Analisis Tentang Potensi IQ, EQ, dan SQ - Abdul Pandi; Muhammad Amri; Mahmuddin (CV Putra Publisher, 2023)
This research is entirely in the nature of library research. Data collected through library research consisting of source data (primary) in the form of books relating to critical studies of Islamic thought. Data processing is entirely